Dracula's Menagerie Reloaded: Assessing the Relative Roles of Habitat and Interspecific Interactions in an Intact Mammalian Assemblage Using Structural Equation Modeling - Marissa A. Dyck; Ruben Iosif; Barbara Promberger–Fürpass; Viorel D. Popescu (Ecology and Evolution)
ABSTRACT Interspecific interactions play a central role in structuring animal communities and food webs. In particular, carnivores are important topdown regulators in ecological communities and the loss of carnivore species can have devastating ecosystem effects. Similarly, carnivore reintroductions are successful if the prey base is sufficient to support population growth, making the case for the importance of bottom‐up regulation processes. As such, rewilding efforts targeted at restoring food webs and natural community regulation processes (trophic rewilding) have become increasingly popular. However, investigations of regulation processes in terrestrial vertebrate communities often take place in heavily altered systems, potentially biasing inference on the presence or importance of top‐down versus bottom‐up regulation processes. Here, we use a stable mammalian assemblage in the Romanian Carpathians to evaluate the relative importance of top‐down and bottom‐up processes and provide a benchmark for understanding the effects and the success of rewilding initiatives. To do so, we used camera trap data from two consecutive years in the Southern Romanian Carpathians and developed hypothesisbased interaction pathways for top‐down and bottom‐up regulation in a piecewise structural equation modeling (SEM) framework. Results from SEMs indicate that while both top‐down (wolf and Eurasian lynx‐driven) and bottom‐up processes (driven by roe deer, red deer, wild boar and hare abundance) play important roles in shaping community structure, landscape characteristics (i.e., terrain ruggedness, road density, elevation, and forest cover) have a greater effect on both predators and prey. The results of this research have implications for rewilding efforts in Europe and globally. This study highlights the importance of preserving natural habitats, underscoring that effective species conservation and coexistence must go hand in hand with conserving natural spaces.